ISOLATION AND CHARACTERIZATION COLLAGEN OF PATIN FISH SKIN (Pangasius Sp.) - Girsang, Valentina; Reveny, Julia; Nainggolan, Marline (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: This study aims to isolate and characterize the collagen isolated from the skin of patin fish.Method: Collagen isolation consisted of three steps, namely deproteinization process using NaOH solution concentration of 0,05 M and long soaking time for 3x24 hours; immersion in CH3COOH solution with a concentration of 0,05 M and long soaking time 3x24 hours; Furthermore, collagen was extracted with water at 40°C for 2 hours. The isolated collagen was tested for characteristics including chemical and physical properties compared to commercial collagen.Results: Chemical characteristics of collagen isolated from patin fish skin isolation compared to commercial collagen, respectively: 6,55% and 6,68% water content; ash content of 0,19% and 0,18%; protein content 93,63% and 97,42% and fat content 0,41% and 0,30%; The metal content in the collagen isolated from the skin of patin fish and commercial collagen is below the threshold (Pb); 0,5 mg/kg. Amino acid test results from patin fish skin collagen obtained glycine (234381,88 mg/kg), proline (109404,17 mg/kg), alanine (83988,79 mg/kg), arginine (80918,44 mg/kg) and glutamate (87315,88 mg/kg). The physical characteristics of the patin fish skin collagen showed the presence of amide group A (3286,7cm-1), amide B (2947,23cm-1), amide I (1651,07cm-1), amide II (1450,47cm-1), and amide III (1246,02 cm-1).Conclusion: Patin fish skin can be isolated into collagen that meets the quality requirements of collagen as a cosmetic preparation.